(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe changes in blood selenium levels in septic shock patients undergoing continuous veno-venous hemofiltration. Subjects and methods: A prospective descriptive study was conducted on 60 septic shock patients receiving continuous veno-venous hemofiltration at the Intensive Care Center of Bach Mai Hospital. Results: Among the 60 patients, the majority were male (68.9%) with a median age of 65 years. The median blood selenium level was 72.02 mcg/L (range: 31.58-272.9 mcg/L) pre-filtration and decreased to 60 mcg/L (range: 16.11-103.91 mcg/L) post-filtration. The proportion of patients with selenium levels below the reference range (80-250 mcg/L) increased from 63.33% pre-filtration to 85% post-filtration. A decrease in selenium levels was observed in 39 out of 60 patients (65%). In these 39 patients, the mean reduction was 25.43 mcg/L, equivalent to 31.88%. The extent of reduction in selenium levels varied significantly between different filtration modalities (CVVH and CVVHDF) and with the application of ultrafiltration during the procedure. The implementation of continuous veno-venous hemofiltration significantly contributed to the decrease in post-filtration selenium levels (p = 0.017). Conclusion: Decreased selenium in septic shock is a common condition, and the reduction of selenium is more severe after venovenous continuous hemofiltration.